Pediatric COVID-19 related myocarditis in multisystem inflammatory syndrome: A case report - Ririe Fachrina Malisie (Paediatrica Indonesiana, 2021)
A number of coronavirus disease-19 (COVID-19)–related myocarditis cases have recently been reported. Myocarditis is an inflammatory disease of the heart characterized by inflammatory infiltrates and myocardial injury without an ischemic cause.1 While multiple etiologies exist, the major cause appears to be related to viral illnesses. Clinical presentations vary from asymptomatic to sudden unexpected death.2 Acute heart failure due to COVID-19-related acute myocarditis has been associated with multisystem inflammatory syndrome, mimicking Kawasaki disease. 3 Here, we report a case of a 1-month old girl with reactive anti-COVID–19 IgG, presenting with arrhythmia following the shortness of breath during hospitalization. Respiratory distress and myocarditis progressed to multiple organ failure and the patient died on her third day in the PICU.